Identification of Existence in Al-Hallaj’s Poetry (Explanatory study) - Abdel Nabi Al-Aqabi, Lect. Dr. Salem (Basra studies journal, 2023)
This title sheds a light on a dual study (humanity and theology), then the concept of solutions and union in al-Hallaj’s poetry. These concepts occupied a large part of the studies of researchers in ancient and modern ones, but they differed in their understanding, due to their being thorny ideas, which led to al-Hallaj falling victim to a distorted understanding because of those concepts that were reflected in his poetic texts. The researcher, in this study, tried to find out the reality of these Sufi concepts according to what he says: his poetic text and in isolation from the historical rulings emanating from a recipient who fell captive to the predetermined formulas of takfir. The interpretive reading revealed a clarity of the existential principles in which he believed - and in particular - after linking it to the theory of existence among the Sufis. Therefore, the contents of the research and its main axes formed answers revealed the reality of the principle (existence) latent in the meanings and contexts of poetic texts for the essence of existence in its two dimensions: (absolute existence, and possible existence). It became clear that the truth of the identity of Dhat al-Hallaj as a (possible) existence in (absolute) existence. It also expressed the great relationship with the trilogy (the self, the beloved, and the language), which led the researcher to make the concept of identification with absolute existence a main title for this research. Accordingly, the study revealed a vision that the form of existence latent under the folds of al-Hallaj’s poetic text represented something completely different from what was drawn by the extremist intellectual projections of which al-Hallaj fell victim.